Follower-Centric Perceptions of Career Advancement Impacted by the LMX Relationship - Hanouni, Dana El (2023)
Followership has been the subject of research papers in leadership, but its coverage resembles a drop in the ocean of leadership research. Its coverage is also more focused on how followership affects leadership. The purpose of this paper is to highlight perceptions of followers when it comes to what affects their career advancement due to their interactions with their managers. Its relevance is in its contribution to the body of knowledge in followership research and the practical applications for organizations, leaders, and HR officers so they can adjust internal systems and processes to better accommodate for followers’ needs to have a successful career advancement. This qualitative research paper examines the LMXderived enablers and inhibitors of follower career advancement. This study extracts those factors from participant interviews conducted by the student researcher and uses qualitative data software to code interviewee transcripts to uncover themes. The participants are millennials who reside in Europe. Five themes were derived for each of the positive and negative factors impacting career advancement. These themes were cross-referenced with literature in the followership and leadership spaces for sense-making.